2017
DOI: 10.25000/acem.336837
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Urotensin II Concentration In Gestational Diabetes

Abstract: Aim: Urotensin II (UII) and its system is implicated in the etiology of many diseases (including diabetes mellitus). We tried in this study to evaluate and compare UII levels in gestational diabetes mellitus (GDM). Methods: Thirty-six pregnant women (15 non-GDM patients consisted group 1 and 21 GDM patients consisted group 2) enrolled in this study. The 3rd group consisted of age matched 22 non pregnant healthy women. Plasma UII levels were determined at the beginning of the study. After 12 weeks of delivery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…11 But in another study, Urotensin II levels were observed to be increased in gestational DM patients in a small-sample study. 8 The increased circulating Urotensin II in the patients with pregnancy complications may be due to the placentae secretes Urotensin II. 19 It could be caused by a lack of conversion of spiral artery, which results in lower blood flow in uteroplacental, resulting in ischemiareperfusion or hypoxia.…”
Section: A C B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 But in another study, Urotensin II levels were observed to be increased in gestational DM patients in a small-sample study. 8 The increased circulating Urotensin II in the patients with pregnancy complications may be due to the placentae secretes Urotensin II. 19 It could be caused by a lack of conversion of spiral artery, which results in lower blood flow in uteroplacental, resulting in ischemiareperfusion or hypoxia.…”
Section: A C B Discussionmentioning
confidence: 99%
“…7 Urotensin II (UII) is a pluripotent vasoactive peptide that is important in the development of insulin resistance. 8,9 In women with GDM, elevated Urotensin II levels are linked to insulin resistance. 9 Urotensin II is the most potent endogenous vasoconstrictor peptide discovered to date.…”
Section: Research Articlementioning
confidence: 99%